Temperature Influence on Chemical Reaction Rates and Gas Formation - Wardana, Dian; Ramadhan , Dwi Sapri; Fahmi, Jaman; Safitri, Wulan Dwi; Everyanti, Ida Cathy; Silalahi, Sarina Septiani; Zubir, Moondra; Siregar, Nurdin (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Reaction rate is fundamentally defined as the change in the concentration of reactants or products perunit time, and is known to be influenced by several determinants, including surface area, temperature,catalysts, and reactant molarity or concentration. The present study specifically investigates the validityof the widely accepted principle that temperature plays a significant role in modulating reaction rates.Experimental variations were introduced, both in terms of temperature levels and the types of chemicalmixtures employed. The findings confirm that temperature indeed accelerates gas generation across alltested reaction systems. However, in mixtures exhibiting higher viscosity, gas formation proceeds moreslowly due to reduced molecular mobility. Consequently, in the softener–baking soda system, the onsetand progression of gas evolution show noticeable differences compared to less viscous mixtures.